Public support for carbon pricing policies and revenue recycling options: a systematic review and meta-analysis of the survey literature - Farah Mohammadzadeh Valencia; Cornelia Mohren; Anjali Ramakrishnan; Marlene Merchert; Jan C. Minx; Jan Christoph Steckel (npj Climate Action)
Abstract Since public support is critical for implementing carbon pricing policies, we conduct a systematic review and meta-analysis to examine the survey-based literature on change in public support for direct and indirect carbon pricing policies with and without revenue recycling options. Following a comprehensive and transparent machine-learning assisted screening of the literature, our dataset comprises 35 studies containing 70 surveys across 26 countries with over 100,000 respondents. We find that the introduction of any type of revenue recycling option increases public support for carbon pricing. Results from our meta-regression indicate that green spending (i.e. using revenues for climate-friendly projects) is the only revenue recycling option associated with a statistically significant increase in public support. Our findings moreover suggest that the effects may depend on which region the survey was carried out, highlighting the need for additional research in countries in the regions of Africa and Latin America and the Caribbean.